Estimation of 10‐year cardiovascular risk among adult population in western Nepal using nonlaboratory‐based WHO/ISH chart, 2023: A cross‐sectional study - Deekshanta Sitaula; Aarati Dhakal; Sujit K. Mandal; Nisha Bhattarai; Amisha Silwal; Pradeep Adhikari; Shikha R. Gupta; Dhan Khatri; Nimesh Lageju; Bhimsagar Guragain (Health Science Reports, 2023)
Abstract Background and Aims Noncommunicable diseases have emerged as a major cause of morbidity and mortality worldwide among which the majority of the deaths are caused by cardiovascular diseases. Estimating the risk of cardiovascular diseases helps eliminate the risk factors and prevent developing cardiovascular diseases in the future. The World Health Organization in association with the International Society of Hypertension has developed risk charts for the estimation of 10‐year risk for cardiovascular diseases. This study aimed to estimate 10‐year cardiovascular risk in the Nepalese population using nonlaboratory‐based charts. Methods A hospital‐based cross‐sectional study was conducted among 314 adults aged 40–74 years visiting the outpatient departments of Shishuwa Hospital in western Nepal. Systematic random sampling was used to select the participants. Questionnaire‐guided short interviews, physical examination, and anthropometric measurements were done. The χ2 test was used to test the significance and a p < 0.05 was considered statistically significant. Results As per the risk estimation charts, high cardiovascular risk (20%–30%) was seen in 6.1% of total participants and moderate cardiovascular risk (10%–20%) was found in 29% of participants. The moderate–high risk was significantly higher among male participants compared to females (p < 0.01). Of all the participants, 22.0% were current smokers, 17.2% were alcohol users, 61.1% were hypertensive, and 35.7% were diabetics. Smoking tobacco, alcohol use, and hypertension were significantly more prevalent among the male participants. (p < 0.01) Adults in the 50–59 years age group had a significantly high prevalence of hypertension (p < 0.01), diabetes (p = 0.02), and alcohol abuse (p = 0.01). Conclusion This study shows high cardiovascular risk among adult population in western Nepal. The 10‐year cardiovascular risk score and risk factors were significantly higher among males than females. There seems to be a prompt necessity of health promotion interventions to reduce cardiovascular risk factors and prevent the burden of cardiovascular diseases in Nepal.